Pendampingan Manajemen Masjid Berbasis Partisipatif Untuk Meningkatkan Kualitas Pengelolaan dan Pelayanan Jamaah di Masjid At-Taqwa Nguwok - Fashi Hatul Lisaniyah; Bahruddin; Sholikatun Fitria (STAI Ma'had Aly Al-Hikam Malang, 2026)
Effective mosque management requires a well-structured management system and active community participation to ensure optimal services for congregants. However, At-Taqwa Mosque in Nguwok Village, Modo District, Lamongan Regency, faces several challenges, including inadequate administrative management, unclear distribution of managerial responsibilities, and limited involvement of mosque youth in mosque activities. Therefore, this community service program aimed to enhance the quality of mosque management and congregational services through participatory mosque management assistance. The program employed a participatory approach consisting of five stages: preparation, needs assessment, program planning, implementation of assistance, and monitoring and evaluation. The participants included mosque administrators (takmir), management board members, and mosque youth. The results demonstrated significant improvements in mosque governance through better administrative practices, strengthened organizational management, more structured work programs, and increased participation of congregants, particularly mosque youth. Furthermore, the program fostered collective awareness regarding the importance of organized, transparent, and sustainable mosque management. These findings indicate that the participatory approach is effective in enhancing the capacity of mosque administrators and supporting the development of the mosque as a center for religious and community activities.